Advances in the Use of Stem Cells in Veterinary Medicine: From Basic Research to Clinical Practice. (9th June 2016) - Markoski, Melissa Medeiros
Abstract : Today, several veterinary diseases may be treated with the administration of stem cells. This is possible because these cells present a high therapeutic potential and may be injected as autologous or allogenic, freshly isolated, or previously cultured. The literature supports that the process is safe and brings considerable benefits to animal health. Knowledge about how adult stem cells modulate the molecular signals to activate cell homing has also been increasingly determined, evidencing the mechanisms which enable cells to repair and regenerate injured tissues. Preclinical studies were designed for many animal models and they have contributed to the translation to the human clinic. This review shows the most commonly used stem cell types, with emphasis on mesenchymal stem cells and their mechanistic potential to repair, as well as the experimental protocols, studied diseases, and species with the highest amount of studies and applications. The relationship between stem cell protocols utilized on clinics, molecular mechanisms, and the physiological responses may offer subsidies to new studies and therefore improve the therapeutic outcome for both humans and animals.